Oral Ferrous Sulphate Improves Functional Capacity on Heart Failure Patients with Iron Deficiency Anemia - Lita Dwi Suryani; Sunu Budhi Raharjo; Rima Sagita; Hansen Angkasa; Yosafat Lambang Prasetyadi; Franciscus D. Suyatna; Nani Hersunarti; Rarsari Soerarso; Bambang Budi Siswanto; Hary Sakti Muliawan (Ubiquity Press, 2022)
Background: Iron deficiency anemia (IDA) in heart failure (HF) is associated with poor functional capacity. Several studies reported the benefit of iron therapy in HF with IDA on improving functional capacity. Therefore, we attempt to investigate the effect of oral iron supplementation on functional capacity in HF patients with IDA. Results: Double blind randomized controlled trial was conducted in National Cardiovascular Center Harapan Kita Hospital Universitas Indonesia. A total 54 HFREF patients with IDA were enrolled and randomized to either oral Ferrous Sulphate (FS) 200mg 3 times a day or placebo with 1:1 ratio for 12 weeks. Primary outcome was functional capacity measured by 6-minute walk test. There were 41 participants completed the study (FS n=22, placebo n=19). Ferrous sulphate significantly improved functional capacity changes (46.23+35m vs -13.7+46m, p<0.001, CI -86.8 to -33.2) compared with placebo groups respectively after 12 weeks intervention. Conclusions: Oral FS supplementation for 12 weeks significantly improved functional capacity in HF patients with IDA. Trial registration: clinicaltrials.gov, NCT02998697. Registered 14 December 2016 - Retrospectively registered, https://clinicaltrials.gov/ct2/show/NCT02998697